THE ROLE OF COMMUNICATION MEDIA IN INTERNATIONAL RELATIONS: PUBLIC DIPLOMACY DURING THE COVID-19 PANDEMIC - ABHARINA NASUTION; CHONTINA SIAHAAN (CV KULTURA DIGITAL MEDIA, 2021)
Due to the pandemic, the mobility of the world community must be limited to stop the spread of COVID-19. However, the country's need to fulfill its national interests, especially in handling the pandemic, must still be met. Conventional diplomatic practice by sending official diplomats to one country is certainly limited this time. The growth in information and communication technology make it easier for every country to be able to carry out public diplomacy as a new diplomatic practice through digital communication media. By using a qualitative approach and descriptive method, the author tries to explain the role of communication media in international relations with a focus on discussing public diplomacy during a pandemic. Through this study, the author finds that social media is very useful in implementing public diplomacy between countries such as South Korea and its entertainment industry actors and China, which is trying to improve its image in order to gain international public support. Both countries fulfill their national interests through electronic communication media.